PERAN PEMERINTAH TINGKAT PROPINSI DALAM UPAYA UNTUK MENDORONG INVESTASI ASING BIDANG PERIKANAN DAN KELAUTAN DI PROPINSI NUSA TENGGARA TIMUR - , YULIANUS SONI KURNIAWAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The role of provincial government in encouraging the foreign investment of fishery and marine sector in his provinces its very important because since Act 32 of 2004 on Regional Autonomy occurred three basic Interchangeability in the local government structure changes in the financial manager, changes Interchangeability manager of natural resources and budget allocation from the center to the regions. Further the law act 25 of 2007 on Investment also confirmed that the provincial government authority in the field of investment are: administrative licensing servants in the field of investment and increased capital investment . NTT Province is a province that relies heavily on central financing so ultimately when government trouble the need for physical infrastructure development is greater than the capital. NTT province has not been able to implement measures to encourage foreign investment the field of fisheries and marine investing in NTT, due to the capital to build the basic infrastructure such as roads, water, and renovation of the new airport is allocated from the center in 2014.